2007
DOI: 10.1111/j.1600-0854.2007.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Trafficking of Potato Leafroll VirusMovement Protein in Transgenic Arabidopsis

Abstract: Intracellular trafficking of viral movement proteins (MPs) in plants has mainly been studied using Tobacco mosaic virus MP30 (TMV MP30) as a model system. Because of the limitations of TMV MP30 expression in Arabidopsis thaliana, these studies have mostly been restricted to tobacco plants. Here we present data on the analysis of transgenic Arabidopsis plants expressing Potato leafroll virus 17-kDa movement protein (MP17) fused to green fluorescent protein. MP17 localizes to secondary branched plasmodesmata (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 70 publications
(117 reference statements)
1
73
0
2
Order By: Relevance
“…5D and 6) suggested the absence or reduced affinity of putative PD receptor proteins and subsequent proteolytic degradation of nontargeted MP17 in senescent leaves, strongly resembling the situation in sink leaves ( Fig. 1; Vogel et al, 2007). In general, leaf senescence is regarded as a developmental process that is induced to recycle and mobilize nutrients for relocation to other plant organs such as reproducing seeds (Lim et al, 2006).…”
Section: Pd Localization and Physiological Consequences Of Mp17:gfp Amentioning
confidence: 99%
“…5D and 6) suggested the absence or reduced affinity of putative PD receptor proteins and subsequent proteolytic degradation of nontargeted MP17 in senescent leaves, strongly resembling the situation in sink leaves ( Fig. 1; Vogel et al, 2007). In general, leaf senescence is regarded as a developmental process that is induced to recycle and mobilize nutrients for relocation to other plant organs such as reproducing seeds (Lim et al, 2006).…”
Section: Pd Localization and Physiological Consequences Of Mp17:gfp Amentioning
confidence: 99%
“…The results obtained by monitoring the movement of sGFP within the RK suggested that PD with a size exclusion limit (SEL) that allows for trafficking of 27-kDa sGFP are present between nSEs. We investigated number and type of PD in RKs on P 35s :MP17-GFP plants (18). MP17 has been shown to specifically target branched, secondary PD (19).…”
Section: Ses Are Nucleate In Rksmentioning
confidence: 99%
“…Concomitantly, we monitored the formation of secondary PD during feeding site development in both RKN-and CN-infested plants expressing a fusion construct of GFP to the potato leafroll virus movement protein MP17 (18). Around both syncytia and GCs, the newly formed SEs were heavily interconnected by PD.…”
mentioning
confidence: 99%
“…Para comprobar que la fluorescencia detectada se limita a membranas celulares se procedió a una tinción específica de membranas con FM64 (Bolte et al, 2004) y con yoduro de propidio (Link et al, 2011;Vogel et al, 2007). En ambos casos, la señal del canal verde de GFP coincide con la señal del canal rojo de cada uno de los colorantes, dando lugar a un color mayoritariamente amarillo en la imagen superpuesta de ambos canales (Figura 18).…”
Section: Figura 14 Tinción Histoquímica Gus De Plantas Transgénicasunclassified
“…Las membranas celulares son impermeables a este compuesto, por lo que se ha utilizado además para la tinción de paredes celulares en células vivas intactas (Link et al, 2011). El protocolo de tinción con yoduro de propidio ha sido descrito previamente (Vogel et al, 2007). Para la tinción de estomas en plántulas de Arabidopsis se incubaron plántulas enteras durante 5 minutos en una solución acuosa de yoduro de propidio 1 µg/ml preparada a partir de una solución stock a 0.1 mg/ml diluída 1:100.…”
Section: Tinción Con Yoduro De Propidiounclassified